2018
DOI: 10.1016/j.bpj.2018.08.044
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Calcium Concentrations Slow Dynamics at the Lipid-Water Interface

Abstract: Phospholipids can interact strongly with ions at physiological concentrations, and these interactions can alter membrane properties. Here, we describe the effects of calcium ions on the dynamics in phospholipid membranes. We used a combination of time-resolved ultrafast two-dimensional infrared spectroscopy and molecular dynamics simulations. We found that millimolar Ca 2þ concentrations lead to slower fluctuations in the local environment at the lipid-water interface of membranes with phosphatidylserine. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 80 publications
(157 reference statements)
4
41
0
Order By: Relevance
“…Recently, a 2D IR study on the effects of Ca 2+ at nearphysiological concentrations showed that interfacial dynamics were slowed down by Ca 2+ but only in membranes containing anionic lipids. 1 Absorption spectra recorded with isotopelabeled anionic lipids indicated that the spectroscopic changes observed were largely localized to the anionic lipids. Similarly, water SFG spectra revealed that NaCl-dependent changes in H-bonding occurred with anionic lipids.…”
Section: Transmembrane Peptides Modulate H-bond Structure and Dynamicsmentioning
confidence: 97%
See 3 more Smart Citations
“…Recently, a 2D IR study on the effects of Ca 2+ at nearphysiological concentrations showed that interfacial dynamics were slowed down by Ca 2+ but only in membranes containing anionic lipids. 1 Absorption spectra recorded with isotopelabeled anionic lipids indicated that the spectroscopic changes observed were largely localized to the anionic lipids. Similarly, water SFG spectra revealed that NaCl-dependent changes in H-bonding occurred with anionic lipids.…”
Section: Transmembrane Peptides Modulate H-bond Structure and Dynamicsmentioning
confidence: 97%
“…R. Valentine, M. L. Cardenas, A. E. Elber, R. Baiz, C. R. Biophys. J.20181151541–1551 This investigation used isotope-edited ultrafast two-dimensional infrared spectroscopy to probe the lipid–water interface of lipid bilayers with and without Ca 2+ in solution. Results indicated a dependence of interfacial dynamics on the Ca 2+ concentration in anionic lipid species.…”
Section: Key Referencesmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, intracellular Ca 2+ can interact with phosphatidylserine in physiological concentration and cause physico-chemical changes, altered hydration in the lipid-water-interface. This in turn alters lipid packing and may slow down interfacial dynamics 56 . Such changes might be useful for the Ca 2+ -dependent desensitization event of wild-type TRPV1.…”
Section: Discussionmentioning
confidence: 99%